mGQM: Evaluation metric for mobile and human interaction - Hussain, Azham; Hashim, Nor Laily; Nordin, Nazib (Springer International Publishing, 2014)
The constant developments in technology of mobile devices are rapidly increasing the demand for applications on these devices.In June 2013, there were 900,000 applications for iPhone available on the iTunes store to be downloaded, and the application store had over 50 billion downloads.Demand for Android phones is also increasing and exceeds analysts’ expectations.As a result of the rapid evolution of mobile device development, a new challenge has emerged for application developers; how to improve the usability of mobile applications.This research examines usability issues of mobile devices, and proposes a metric based model which may be used to evaluate applications on mobile devices.